Case studies in engineering design - Matthews, Clifford
A multidisciplinary introduction to engineering design using real-life case studies. Case Studies in Engineering Design provides students and practising engineers with many practical and accessible case studies which are representative of situations engineers face in professional life, and which incorporate a range of engineering disciplines. Different methodologies of approaching engineering design are identified and explained prior to their application in the case studies. The case studies have been chosen from real-life engineering design projects and aim to expose students to a wide variety of design activities and situations, including those that have incomplete, or imperfect, information. This book encourages the student to be innovative, to try new ideas, whilst not losing sight of sound and well-proven engineering practice. A set of notes for lecturers to accompany the book is available free to download from: http://www.bh.com/manuals/0340691352 * A multidisciplinary introduction to engineering design. * Exposes readers to wide variety of design activities and situations. * Encourages exploration of new ideas using sound and well-proven engineering practice.